Pengaruh Return On Asset Dan Dividend Payout Ratio Terhadap Nilai Perusahaan - Irma Lusiana; Lusiana, Irma; Usdeldi, Usdeldi; Fitrianova Andriani, Beid (Manajemen Keuangan Syariah, 2023)
This research is based on the company's value showing fluctuating conditions in Food and Beverage Sub-Sector companies from 2019 to 2021, as well as the inconsistent influence between the variables Return On Assets and Dividend Payout Ratio on company value from the results of previous research. The purpose of this study was to determine the effect of Return On Asset and Dividend Payout Ratio on Company Value in the Food and Beverage Sub-Sector Listed on the Indonesian Sharia Stock Index for the 2019-2021 period. This research uses a quantitative approach and the data analysis method used is panel data regression analysis. The samples used in this study were as many as 10 companies with a total sample for 3 years, namely 30 samples, using purposive sampling selection techniques. The results of this study show that the Return On Asset variable has a significant effect on the company's value, while the Dividend Payout Ratio variable has no effect on the company's value. This research also shows that together the variables Return On Asset and Dividend Payout Ratio have a significant influence on the value of companies in the Food and Beverage Sub-Sector listed on the Indonesian Sharia Stock Index (ISSI) for the 2019-2021 period with the value of the coefficient of determination for this model is 18.50%. Keywords : Company Value, Dividend Payout Ratio, Return On Assets.